1001 Analyzing 4-year Estimates Of Sleep Duration And Quality Among 2 Million Users Of A Sleep Tracker In New York City. (12th April 2019) - Seixas, Azizi; Robbins, Rebecca; Affouf, Mahmoud; Beaugris, Louis; Donley, Tiffany; Moore, Jesse; Richards, Shannique; Jean-Louis, Girardin
Abstract: Introduction: Population estimates for sleep duration and quality are inconsistent because they rely on self-report and smaller samples using objective data. Tracking and wearable devices may provide more accurate estimates of sleep duration and quality. In this study, we investigated estimates of sleep duration and quality among 2 million users of a mobile sleep application in an urban city in the United States (U.S.). Methods: We examined sleep duration and quality from 2, 194, 897 users of SleepCycle, a popular sleep tracking app. over a four-year period (2015 to 2018). In this analysis, we specifically explored differences in sleep duration and quality by demographic factors, including age and sex. We utilized graphical matrix representations of data (heat maps) and geospatial analyses to compare sleep duration (in hours) and sleep quality (based on a composite score amalgamating time in bed, deep-sleep time, sleep consistency, and amount of times fully awake), considering potential effects of day of the week and seasonality. Results: Among SleepCycle users, 45.6% (n=1, 001, 335) were female. The average age of the sample was 31.0 years. The mean sleep duration of the total sample was 7.11 hours; women slept longer than did men (M=7.27 hours vs. M=7.00 hours, p<.001). Increasing age tended to be associated with longer sleep duration and better sleep quality. Results also showed sleep duration was longer on weekends (M=7.19 hours), compared to weeknights (M=7.09 hours). Sleep duration was longest (M=7.18 hours) during the winter, but shortest during the summer (M=7.11 hours). Sleep quality was highest (M=72.75) during the winter, but lowest during the summer (M=71.99). Conclusion: Our findings from big data are consistent with previously reported estimates of sleep duration and quality. Sleep duration varied by age, sex, day of the week, and season. Future studies should determine whether estimates of sleep duration and quality are affected by environmental factors such as geographic location. Support (If Any): NHLBI K01HL135452, NIA K07AG052685